Inner-Biblical Exegesis as a Form of Reception: A Clarification of Methodology - Yohanes Tjin (RERUM: Journal of Biblical Practice, 2022)
There are certain assumptions with inner-biblical exegesis which, in light of reception theory, can not be maintained. Reception theory stresses the social context and function of the act of reading which is also present in inner-biblical exegesis and must be analyzed. Hence, a proper methodology is needed to study inner-biblical exegesis. Through comparative analysis between reception theory and inner-biblical exegesis, in this article, I argue that inner-biblical exegesis can be seen as a form of reception. Two distinctive features of inner-biblical exegesis—directionality and intentionality—fit nicely with the concept in reception theory—the first- and second-degree texts. Furthermore, seeing inner-biblical exegesis as a form of reception necessitates an understanding of its social function as it is influenced by and seeks to influence its social-historical context. Therefore, studying inner-biblical exegesis is not only limited to identifying strategies of interpretation but also its social-historical context and, hence, its social function.